The Declaration of Madrid.Psychiatric ethics in the light of the Ethical Declarations - Hącia , Artur (Current Problems of Psychiatry, 2015)
Psychiatry is the medical specialty and psychiatrists face ethical and deontological dilemmas and questions similar to their medical colleagues from different specialties. One way to address such situations is to reference certain principles and codes that are the result of the ethical considerations of the medical community. An excellent example of this is the Hippocratic Oath to which doctors have referred for hundreds of years. Psychiatry is a very young medical discipline that emerged only 250 years ago. Until the mid-20th century, the ethical rules of psychiatry were only governed by medical codes of ethics common to all medical professionals. Only with the recent, intensive development of psychiatry following many abuses and misuses of the World War II, have psychiatrists developed special principles of ethics unique to psychiatry. This paper discusses the historical background of the difficulties confronting the development of psychiatry, including its past abuses, and then shows the significant impact of this history on the development of the ethical documents related to psychiatry. The crimes and the abuses of World War II are among the most significant factors considered here. Among many the medical codes of ethics, The Nuremberg Code (1947), The Declaration of Geneva(1948), The International Code of Medical Ethics (1964) and The Declaration of Tokyo (1975) deserve mention. Finally, psychiatrists have adopted the documents directed particularly for themselves. Among the first psychiatric codes of ethics implemented were The Principles of Medical Ethics with Annotations Especially Applicable to Psychiatry issued by APA in USA (1973), The Declaration of Hawaii (1977) and later, The Declaration of Madrid, issued by WPA (1996). Presently, the WPA continues to develop their project, The Code of Psychiatric Ethics. In this paper, the above-mentioned documents are described in the context of their formation, evolution and upgrading. This paper also presents the expectations and plans for the comprehensive development of ethical thought in the field of psychiatry. Aside from the adoption of ethical codes for psychiatry, it is also necessary to develop appropriate ethical personal attitudes and properly formed consciences, because without these, ethical codes and oaths alone cannot protect against further abuses and crimes in the field.